PSK Dan Nilai Agama: Studi Tentang Pilihan Rasional Pekerja Seks Komersial - Mohammad Maulana Iqbal; Imam Muklas; Fitriani Dina Atmaja; Mochamad Fadhilah Akbar; Agus Mahfud Fauzi (Institut Agama Islam Negeri Palopo, 2022)
Based on the legal provisions and the existing norm values that CSWs are prohibited in Indonesia. However, CSWs are still commonly found in social life. The research began with a Chinese funeral complex, Kembang Kuning Surabaya, which was used as the location of a prostitute. The research objective is to identify the position of religious values in CSWs, identify social reality in CSWs, and identify a person's rational choice to become CSWs. While the research method used is descriptive qualitative through data collection techniques according to observation and interviews. James S. Coleman's rational choice theory is used to analyze the data found. The results showed that the position of religion still exists within a prostitute. The responsibility to make ends meet and the demands to pay large amounts of debt are the reasons for someone to become a prostitute.